2020
DOI: 10.22581/muet1982.2001.20
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Topic Modeling Approach for Text Mining and Information Retrieval through K-means Clustering

Abstract: Topic modeling is an effective text mining and information retrieval approach to organizing knowledge with various contents under a specific topic. Text documents in form of news articles are increasing very fast on the web. Analysis of these documents is very important in the fields of text mining and information retrieval. Meaningful information extraction from these documents is a challenging task. One approach for discovering the theme from text documents is topic modeling but this approach still needs a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This study showed that pre-processing of data prior to model building enhances prediction accuracy ( 35 ). Machine learning methods are also used for the detection of some other medical diseases detection ( 36 38 ), text mining ( 39 42 ) and network security ( 43 47 ). Another analysis is conducted to predict the risks associated with diabetes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study showed that pre-processing of data prior to model building enhances prediction accuracy ( 35 ). Machine learning methods are also used for the detection of some other medical diseases detection ( 36 38 ), text mining ( 39 42 ) and network security ( 43 47 ). Another analysis is conducted to predict the risks associated with diabetes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed policy was compared to first-in-first-out and multi-priority-discipline queue strategies with the help of a complete study of wait times and gaps in wait times [23][24][25]. Machine learning and Clustering based various methods are used for the text analysis [26], internet of things [27][28][29][30][31][32][33], and disease detection [34]. Under any given IoT workload, the mathematical model estimates the minimum number of fog nodes required to meet QoS requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Khurana and Verma [25] introduced a new algorithm to solve high-dimensionality, named modified biogeographybased optimization, which uses a feature weighting algorithm to modify the ranking of variables. Rashid et al [26] proposed new k-means topic modeling to capture better semantic topics.…”
Section: Feature Selection For Text Classificationmentioning
confidence: 99%